2016
DOI: 10.1016/j.pmcj.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Fine-grained appliance usage and energy monitoring through mobile and power-line sensing

Abstract: To promote energy-efficient operations in residential and office buildings, non-intrusive load monitoring (NILM) techniques have been proposed to infer the fine-grained power consumption and usage patterns of appliances from power-line measurement data. Fine-grained monitoring of everyday appliances (such as toasters and coffee makers) can not only promote energy-efficient building operations, but also provide unique insights into the context and activities of individuals. Current building-level NILM technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, there are still errors in identifying the appliances with similar PQ characteristics when only low-frequency power and active power are used. In [22], the authors analyzed monitored power data and found that the power consumption pattern of appliances was useful in identifying them. The power sequences of typical household appliances from AMPds are extracted, and the power consumption curves in Figure 2 are provided to illustrate their power consumption pattern.…”
Section: Load Signature Analysismentioning
confidence: 99%
“…However, there are still errors in identifying the appliances with similar PQ characteristics when only low-frequency power and active power are used. In [22], the authors analyzed monitored power data and found that the power consumption pattern of appliances was useful in identifying them. The power sequences of typical household appliances from AMPds are extracted, and the power consumption curves in Figure 2 are provided to illustrate their power consumption pattern.…”
Section: Load Signature Analysismentioning
confidence: 99%
“…The applicability of using user WiFi data to localize appliance usages is discussed in [13]. In a similar vein location and activity has been used in [14] to reduce the search space of disaggregation from contextual information.…”
Section: Related Workmentioning
confidence: 99%
“…Based on the disaggregation of energy usage, ADL patterns can be established in a simple, unobtrusive, and inexpensive way [ 19 ]. By disaggregating the total energy load, it is possible to determine which appliances are being used on a certain day [ 20 - 23 ]. This technique, also known as nonintrusive load monitoring, makes it possible, by using algorithms, to infer the fine-grained energy usage patterns of different appliances in the household [ 20 , 24 - 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…By disaggregating the total energy load, it is possible to determine which appliances are being used on a certain day [ 20 - 23 ]. This technique, also known as nonintrusive load monitoring, makes it possible, by using algorithms, to infer the fine-grained energy usage patterns of different appliances in the household [ 20 , 24 - 26 ]. This energy usage pattern could be linked to health-related activities, such as cooking, which can therefore be used as a proxy for the general health and safety of the persons living in this household and possibly anticipate accidents or hospitalization [ 27 ].…”
Section: Introductionmentioning
confidence: 99%